2006
DOI: 10.1111/j.1469-0691.2006.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal osteoarticular infections in patients treated at a comprehensive cancer centre: a 10-year retrospective review

Abstract: This study reviewed retrospectively the clinical characteristics of 28 cancer patients with fungal osteoarticular infections (FOAIs) between 1995 and 2005. Most patients (26; 93%) had haematological malignancies (19 had leukaemia); half (14) were allogeneic stem-cell transplant recipients. Twelve patients (43%) had severe neutropenia (< or = 100/mm3) with a mean duration of 65 days (range 10-500 days), and ten (36%) patients had received a significant dose of corticosteroids. Most (19; 68%) FOAIs were caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 22 publications
0
28
0
5
Order By: Relevance
“…Only five of those cases were caused by mucoraceous moulds. Of the 28 cases, only two were classified as septic arthritis (Kumashi et al , 2006). There have been a few case reports of mucoraceous mould causing septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Only five of those cases were caused by mucoraceous moulds. Of the 28 cases, only two were classified as septic arthritis (Kumashi et al , 2006). There have been a few case reports of mucoraceous mould causing septic arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Drainage should be performed to gain synovial fluid for diagnostic methods. While debridement and drainage are indicated in Aspergillus arthritis, joint replacement can only be recommended in selected cases . Steinfeld et al .…”
Section: Arthritismentioning
confidence: 99%
“…While debridement and drainage are indicated in Aspergillus arthritis, joint replacement can only be recommended in selected cases. [92][93][94][94][95][96][97][98][99][100] Steinfeld et al [99] reported of two cases of Aspergillus arthritis of the knee that were managed by surgical intervention after the poor response to antifungal therapy alone. Arthroscopic debridement with a motorised shaver was performed and both patients showed good response.…”
Section: Pleuritismentioning
confidence: 99%
“…Fungi reported as causative agents of osteomyelitis include Candida species, Aspergillus species, Cryptococcus species , Fusarium species , Pseudallescheria boydii, Zygomycetes , and endemic dimorphic fungi, including Histoplasma capsulatum, Blastomyces dermatitidis , and Coccidioides species (1). Aspergillus osteomyelitis has been noted as a result of dissemination in solid organ transplant recipients.…”
mentioning
confidence: 99%